Entrepreneurship and economic growth: A cross-sectional analysis perspective - Jungsuk Kim; Cynthia Castillejos-Petalcorin; Yothin Jinjarak; Donghyun Park; Pilipinas Quising; Shu Tian (Asian Development Bank (ADB), 2022)
Entrepreneurship, or the activity of starting and running a business, is a vital ingredient of economic growth and development. Entrepreneurs contribute to innovation, and they are central to dynamic Schumpeterian competition and broader economic dynamism. In this paper, we contribute to the entrepreneurship literature by performing cross-sectional analysis to examine the link between entrepreneurship and economic growth. We divide total early-stage entrepreneurship into opportunity-driven entrepreneurship versus necessitydriven entrepreneurship, and our sample economies into advanced economies versus developing economies. We do not find evidence of a positive link between aggregate entrepreneurship and economic growth. This is consistent with the hugely heterogenous nature of entrepreneurial activity. At a broader level, our empirical evidence points to the importance of distinguishing between different types of entrepreneurship and different groups of economies. In particular, for developing economies where manufacturing is relatively important, we find that opportunity-driven entrepreneurship is positively linked with growth.
Keywords: L26; M13; O47; 330; entrepreneurship; economic growth; development